An anatomic variant caudate lobe in a cadaver - Chhabra, Neeta; Shrivastava, Tripti; Garg, Lalit; Mishra, B. K. (International Journal of Research in Medical Sciences, 2017)
The liver can present a number of congenital anomalies. Most common among them are the irregularities in shape and the number of lobules. Less common variations include presence of accessory lobes or accessory fissures. The accessory lobe may be attached to the liver through a mesentery or a bridge of hepatic tissue and they are usually asymptomatic. An accessory liver lobe though a very rare occurrence but when it exists it becomes clinically important because of its rarity. We are reporting one such case of accessory caudate lobe of liver found during routine dissection of embalmed cadaver of a 60 year old male. It was separated from the caudate lobe by a well-defined fissure. The quadrate lobe and fissure for ligamentum teres were totally absent. Ligamentum teres was found embedded in the substance of the liver on its inferior surface. The presence of additional lobes and fissures or the absence of normal lobes and fissures might lead to confusion during surgery or clinical misdiagnosis. Knowledge and awareness of these anomalies is useful to the clinician to rule out diseases, surgeons during segmental resection of liver and radiologist when interpreting liver radiologic findings.